2015
DOI: 10.3109/19396368.2015.1101510
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol prevents experimentally-induced oxidative damage to membrane lipids and nuclear DNA in porcine ovary

Abstract: Estrogens, with their principle representative 17β-estradiol, contribute to the redox state of cells showing both pro- and antioxidative properties. In the ovary, being the main source of estrogens, maintaining balance between the production and detoxification of ROS is crucial. Whereas ovary estrogen concentration is difficult to estimate, its circulating concentration in women may reach the nanomolar level. The aim of the study was to evaluate the effects of 17β-estradiol on oxidative damage to membrane lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 37 publications
5
26
0
Order By: Relevance
“…The biomarker, 8-OHdG, released secondary to DNA damage, is regarded as the most significant indicator of DNA damage. 52,53) Hydroxyl radicals eliminate hydrogen from nucleic acids or react with double bonds, leading to 8-OHdG. 54) There have been various studies suggesting that DNA damage decreases by anti-oxidant augmentation, 55,56) and our results in the current study support these findings, wherein naringenin utilized its anti-oxidant properties to decrease ROS-mediated 8-OHdG levels indicating the inhibition of oxidative DNA damage.…”
Section: Discussionsupporting
confidence: 78%
“…The biomarker, 8-OHdG, released secondary to DNA damage, is regarded as the most significant indicator of DNA damage. 52,53) Hydroxyl radicals eliminate hydrogen from nucleic acids or react with double bonds, leading to 8-OHdG. 54) There have been various studies suggesting that DNA damage decreases by anti-oxidant augmentation, 55,56) and our results in the current study support these findings, wherein naringenin utilized its anti-oxidant properties to decrease ROS-mediated 8-OHdG levels indicating the inhibition of oxidative DNA damage.…”
Section: Discussionsupporting
confidence: 78%
“…Concerning the ovaries, iron excess can directly suppress female gonadal function [ 6 ]. Both substrates of the Fenton reaction (Fe 2+ and H 2 O 2 ) can be used to experimentally induce oxidative damage in macromolecules, such as lipids, protein, and DNA [ 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Estradiol could induce granulose cella and cumulus cell functional changes (Couse et al, 2005). Stepniak & Karbownik-Lewinska (2016) found that under physiological conditions estradiol contributed to protecting the ovary against oxidative damage to membrane lipids and nuclear DNA in porcine ovary. Coinciding with the previous studies, the present study indicated that melatonin stimulated the secretion of progesterone and estradiol in COCs, and the progesterone and estradiol production was higher in the 30 pmol mL −1 melatonin-treated group.…”
Section: Discussionmentioning
confidence: 97%